6: Enhancing Out-of-Class Communication - Farley‐Lucas, Bonnie S.; Sargent, Margaret M. (To Improve the Academy, 2011)
Out-of-class communication between faculty and students is linked to student learning, engagement, and success. As the source for mentoring, advising, and supplemental instruction, out-of-class communication and its barriers require explicit attention. Using a faculty-student collaborative research approach, we interviewed a diverse group of thirty-three undergraduates regarding behaviors, statements, and practices that contributed to or discouraged out-of-class communication. We found that in-class communication sets the stage for whether students approach faculty outside class and that faculty misbehaviors and disconfirming communication in class almost inevitably lead to out-of-class avoidance.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/099-255-442-821-233, pop00355
Keywords: dept.com